Cosmology and moral community in the Lakota Sun Dance - Detwiler, Fritz, 1947- author.
1 online resource.
Keywords: "Drawing on Indigenous methodologies, this book uses a close analysis of James R. Walker's 1917 monograph on the Lakota Sun Dance to explore how the Sun Dance communal ritual complex-the most important Lakota ceremony--creates moral community, providing insights into the cosmology and worldview of Lakota tradition. The book uses Walker's primary source to conduct a reading of the Sun Dance in its nineteenth-century context through the lenses of Lakota metaphysics, cosmology, ontology and ethics. The author argues that the Sun Dance constitutes a cosmic ethical drama in which persons of all types - human and non-human -- come together in reciprocal actions and relationships. Drawing on contemporary animist theory and a perspectivist approach that uses Lakota worldview assumptions as the basis for analysis, the book enables a richer understanding of the Sun Dance and its role in the Lakota moral world. Offering a nuanced understanding that centers Lakota views of the sacred, this book will be relevant to scholars of religion and animism, and all those interested in Native American cultures and lifeways"--